Bactericidal Effects of Exiguobacterium sp GM010 Pigment Against Food-Borne Pathogens - Mekala, Krishna-Prashanth Ramesh; Pandit, Saritha G.; Dhale, Mohan A. (Frontiers in Sustainable Food Systems, 2020)
Bacterium producing yellowish-orange pigment was identified (morphological, biochemical and 16S rRNA) as Exiguobacterium sp GM010. The UV-visible spectrum of Exiguobacterium sp GM010 extract showing λ max at 465nm revealed orange pigment characteristic. Pigment showed broad spectrum antibacterial action against gram positive and gram negative food-borne pathogens. The SYTO9 and propidium iodide (PI) staining revealed the cell membrane damage of food-borne pathogens under confocal laser scanning microscop (CLSM) indicating the bactericidal effect. This was evidenced by the fourier transform infrared (FTIR) spectrum, showing characteristic functional groups that mainly included hydroxyl, carbonyl and carboxylic groups causing a system of delocalized electrons leading to destabilization of membrane and decrease in membrane potential that resulted in bactericidal effect. The pigment of Exiguobacterium sp GM010 were nontoxic against Artemia franciscana and can be a promising source to control the food-borne pathogens in food industries.